THE NEED OF EDUCATION - Nigora Normurodova Shokirovna, Yuldoshev Tojiddin Abdukarimovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2024)
Education is not how well you can read and write but whether you can communicate with and understand the world around you. A good education not only teachers you skills but also helps you broaden your horizons, gain better perspective, and teachers you to think for yourself. People today are quite aware and comfortable speaking about social injustices and other pressing issues. This can be attributed to the increased access to education around the world, which in turn has made society more accepting and open-minded. Therefore,education is an element of human evolution.